Peculiarities of hydrogen negative ion beams extraction from axially symmetric source with crossed fields - Goretskii, V.P.; Dobrovolskiy, A.M. (Вопросы атомной науки и техники, 2015)
A comparison of emission features of axially symmetric H⁻ ion source with magnetron discharge and H⁻ source which incorporates additional hollow cathode discharge in series with main one is presented. It is shown that in the last case concentration of H⁻ ions in a region of emission hole of the source essentially increases. H⁻ ion current from the source with additional discharge increases by an order of magnitude. Additional plasma drift from assisting discharge and cooling of electrons at their passing through magnetic field region are considered as the reasons of determined growth of concentration of negative ions. H⁻ current density value of 150 mA/cm2 on emission aperture of ion source is reached. Приводится сравнение эмиссионных свойств источника ионов Н⁻ с осевой симметрией с магнетронным разрядом и источника Н⁻, в котором последовательно с основным дополнительно горит разряд типа «полый катод». Показано, что в последнем случае существенно возрастает концентрация ионов Н⁻ в области эмиссионного отверстия источника. Ток ионов Н⁻ из источника с дополнительным разрядом увеличивается на порядок величины. В качестве причин обнаруженного увеличения концентрации отрицательных ионов рассматриваются дополнительный дрейф плазмы из области вспомогательного разряда и охлаждение электронов при прохождении области с магнитным полем. Достигнутая величина плотности тока Н⁻ в пересчете на эмиссионную апертуру источника составила не менее 150 мА/см², что в полтора раза превышает ранее полученные результаты. Наведено порівняння емісійних властивостей джерела іонів Н⁻ з симетрією навколо oсі з магнетронним розрядом із джерелом Н⁻, в якому додатково до основного запалюється розряд типу «порожнистий катод». Показано, що в останньому випадку значно зростає концентрація іонів Н⁻ в області емісійного отвору джерела. Струм іонів Н⁻ iз джерела з додатковим розрядом збільшується на порядок величини. В якості причин виявленого збільшення концентрації негативних іонів розглядається додатковий дрейф плазми з області допоміжного розряду та охолодження електронів при проходженні області з магнітним полем. Досягнута величина густини струму іонів Н⁻ у перерахунку на емісійну апертуру джерела становить не менше ніж 150 мА/см², що в півтора рази перевершує попередні результати.